The Role of The Ministry of Women’s Empowerment and Child Protection in Overming The Level of Cases of Sexual Violence Against Children in Indonesia - Andiny Pratiwi Putri; Timbul Dompak (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Seven development agendas have been established in compliance with Presidential Regulation Number 18 of 2020 about the National Medium-Term Development Plan (RPJMN) 2022–2024. The Indonesian government is particularly concerned about the rising number of child sexual assault cases each year. Finding out how the Ministry of Women's Empowerment and Child Protection contributes to reducing the number of child sexual abuse cases in Indonesia is the aim of this study. A qualitative approach utilizing a literature study methodology is the research methodology employed. According to the study's findings, one of the most crucial issues and a top goal of Indonesian government policy is protecting children from sexual abuse, KPPPA acts as a Prevelence of Violence Against Children (KtA) by conducting training on national strategies for eliminating sexual violence against children, building a Child Friendly Regency / City Program (KLA). In addition, KPPPA collaborates with local governments, educational institutions, communities, and other stakeholders to create a safer environment for children. However, several challenges remain, including limited public awareness, differences in regional capacity, underreporting of cases, and the need for stronger coordination among institutions. Therefore, optimizing prevention programs, improving institutional capacity, and strengthening collaborative efforts are necessary steps to reduce child sexual abuse cases and ensure comprehensive child protection in Indonesia.